Modeling and simulation of organisational knowledge creation process with consideration of dialogue. (3rd November 2022) - Iinuma, Morihiko; Shiba, Naoki; Homma, Miyako; Saito, Toshio
In adaptation to a changing environment, innovation is essential for continuing existence of an organisation. Of the many approaches available for research on innovation, the present study performed by taking the perspective of knowledge management. The central point of discussion is organisational knowledge creation, where it was considered and modelled with basic recognition of the important role of dialogue between organisation members, a role comprising the two phases of knowledge creation at the individual level and diffusion of the created knowledge. Exploratory investigation by simulation on factors that affect organisational knowledge creation shows that a trade-off exists between knowledge creation at the individual level and diffusion of the created knowledge, and that skilful maintenance of the balance between them is a key task in knowledge management.